Network security with pfSense : architect, deploy, and operate enterprise-grade firewalls - Aggarwal, Manuj (Packt Publishing, 2018)
PfSense is the world's most trusted open source network security solution. In this book, you'll learn about pfSense, all of its key features, how you can install and deploy it, as well as the different tasks you can perform.